Telaah Kritis Praktik Pendistribisuan Dan Manfaat Zakat Fitrah Di Desa Ngadirojo Soko Ponorogo Tahun 2019 - Ahmad Royani; Yayuk Ambar Wati (At-Tasyri': Jurnal Hukum dan Ekonomi Syariah, 2020)
Abstract Zakat fitrah is a zakat that must be issued by every individual who is Muslim whose time is related to the holy month of Ramadan. The purpose of zakat fitrah is to purify the soul and fulfill the needs of the needy and poor people on Eid al-Fitr. For the determination of mustahiq must be exactly as specified in Islamic law so that the purpose of zakat fitrah implemented.The practice of managing zakat fitrah in Ngadirojo Village, Sooko District, Ponorogo Regency is left to each mosque in the village. The distribution is carried out by distributing zakat fitrah to people in need and orphanages. But there are still mosques where the distribution of zakat fitrah is distributed evenly by the zakat committee to local residents without looking and considering the economic situation as a mustahiq. In the village there is also one mosque that utilizes zakat fitrah for khataman activities at the end of Ramadan. Why is zakat fitrah in one mosque in Ngadirojo village distributed evenly to local residents without looking at the poor or rich and why does zakat fitrah be used for religious activities? then how about a review of Islamic Law on these practices? This type of research conducted in this study is field research, namely data obtained from direct searches regarding the management of zakat fitrah in Ngadirojo Village, Sooko District, Ponororgo Regency. In getting the data, the compiler made observations and interviews directly to Mudin (zakat fitrah manager in Ngadirojo Village), zakat fitrah committee, and local residents. While the approach that the authors did in this study uses a normative approach, which is to solve the problem using the Qur'an, the hadith, and opinions of the scholars. In analyzing the constituent data using qualitative analysis by analyzing all data collected then described by the inductive method.The practice of the distribution of zakat fitrah in some mosques in Ngadirojo Village distributed to people in need and orphanages is in accordance with Islamic Law. But the distribution of zakat fitrah which is distributed evenly and the use of zakat fitrah for khataman events at the Ar-Rohmah Mosque, Hamlet Wates, Ngadirojo Village cannot be justified in Islamic Law because it does not match what is stated in the Koran at-Taubah verse 60 and not in accordance with the Prophet's hadith.